OPTIMALISASI PEMANFAATAN LIMBAH ABUTA (ABU SEKAM PADI, DAN SERBUK BATA) SEBAGAI SUBTITUSI SEMEN PADA CAMPURAN BETON RAMAH LINGKUNGAN - Wicaksono, Teguh Mulyo; Mukhlisin, Muhammad; Fatmawati, Leily; Rahmawati, Roselina; Supriyadi, Supriyadi; Sukoyo, Sukoyo; Sudarmono, Sudarmono; Herlambang, Fajar Surya; Anastasya, Frida (Bangun Rekaprima, 2024)
Construction prioritizes the strength of concrete without thinking about the negative impact on the environment. The cement industry is estimated to contribute 5-7% of CO2 gas emissions in the world. On the other hand, Indonesia is also faced with environmental problems caused by various industrial waste. From this problem an innovation emerged, namely ABUTA (husk ash and brick ash). The aim of this innovation is to create a concrete innovation using Abuta Waste (Rice Husk Ash, and Brick Powder). For the manufacture of economical, environmentally friendly concrete to reduce the negative impacts caused by excessive use of cement and reduce industrial waste in Indonesia. In writing this proposal the author used the experimental writing method and data collection method. The concrete innovation applied is concrete with a mixture of variations in the composition of rice husk ash powder and red brick powder of 10% of the cement composition in conventional concrete so that it is more economical and environmentally friendly. In this study, the ACI (American Concrete Institute) mix design method was used with the required design quality of 30 MPa. It is hoped that this innovation can become an environmentally friendly concrete innovation to reduce the negative impacts of excessive cement use and reduce industrial waste in Indonesia. Based on the mix design, the proportion of ash mixture (rice husk ash and brick powder) is 1:1. Meanwhile, the ratio of the amount of ash mixture to cement is 10%: 90%. The compressive strength of concrete with a 0% Abuta mix variation (7 days old) was 19.5, while the concrete innovation with a 10% Abuta mix variation (7 days old) was 15.70 Mpa. This means that the 10% mixture reduces the compressive strength value by 46.28% below the 0% abuta mixture variation. Using a mixture of 10% ash (rice husk ash and brick powder) in innovative concrete can reduce production costs by IDR. 76,700/m ³. Based on the materials obtained in this manufacture, it can be concluded that to obtain optimal compressive strength, better quality materials are needed. The application of concrete can be applied in casting work floors and non-structural construction work such as buildings that require general load power such as housing, sculpture, home interiors and others.